ANALISIS LEGAL STANDING BAGI CALON ANGGOTA LEGISLATIF DALAM PERKARA PERSELISIHAN HASIL PEMILIHAN UMUM - Zuama, Ayuta Puspa Citra; Isharyanto, Isharyanto (Res Publica: Jurnal Hukum Kebijakan Publik, 2020)
The research analyzes and examines the legal standing of prospective legislative members (caleg) House of Representatives (DPR) and regional People’s Representative Council (DPRD) In application for settlement of the general election dispute (PHPU) In the Constitutional Court (MK) and its implications for the role of political parties.This research uses secondary data, that consist of primary legal material and secondary legal material, Compiled through literature studies. This research shows that the MK has made new provisions The extension of legal standing for the individual prospective legislative members DPR and DPRD To apply for a PHPU settlement through PMK 2/2018. However, the provision of legal standing is not fully able to provide access to electoral justice for the individual DPR and DPRD, Due to the provisions of the terms of consent of the relevant political party so that the application can be examined, tried, and terminated by the COURT. It also shows that the role of the political party in the process of filing a lawsuit application to the MK is still very influential and so important. Decisions of political parties are still very decisive.